2014
DOI: 10.3389/fnagi.2014.00291
|View full text |Cite
|
Sign up to set email alerts
|

Holistic face perception in young and older adults: effects of feedback and attentional demand

Abstract: Evidence exists for age-related decline in face cognition ability. However, the extents to which attentional demand and flexibility to adapt viewing strategies contribute to age-related decline in face cognition tests is poorly understood. Here, we studied holistic face perception in older (age range 65–78 years, mean age 69.9) and young adults (age range 20–32 years, mean age 23.1) using the complete design for a sequential study-test composite face task (Richler et al., 2008b). Attentional demand was varied … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
17
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 67 publications
(96 reference statements)
3
17
1
Order By: Relevance
“…While the scanning patterns recorded in Experiment 1 are consistent with evidence that the eyes play a dominant role in face identification (e.g., McKelvie, 1976;Fraser, Craig, & Parker, 1990;Haig, 1985Haig, , 1986Tanaka & Farah, 1993;Walker-Smith, 1978), those recorded in Experiment 2 indicate that this is not the only route by which faces can be efficiently processed. This finding is consistent with behavioral studies demonstrating that task requirements can influence the manner in which faces are analyzed (Gao et al, 2011;Meinhardt-Injac, Persike, & Meinhardt, 2014). …”
Section: Discussionsupporting
confidence: 80%
“…While the scanning patterns recorded in Experiment 1 are consistent with evidence that the eyes play a dominant role in face identification (e.g., McKelvie, 1976;Fraser, Craig, & Parker, 1990;Haig, 1985Haig, , 1986Tanaka & Farah, 1993;Walker-Smith, 1978), those recorded in Experiment 2 indicate that this is not the only route by which faces can be efficiently processed. This finding is consistent with behavioral studies demonstrating that task requirements can influence the manner in which faces are analyzed (Gao et al, 2011;Meinhardt-Injac, Persike, & Meinhardt, 2014). …”
Section: Discussionsupporting
confidence: 80%
“…Middle-age adults were strongly biased toward “same” responses, while young adults and adolescents had no global response preference. A global bias toward “same” responses was also reported for older subjects in the age range of 65–78 years for the composite face task (Meinhardt-Injac et al, 2014a ). This indicates that the most frequent error of older adults in face comparisons is overlooking the difference.…”
Section: Discussionmentioning
confidence: 66%
“…Roudaia et al ( 2008 ) studied contour integration performance and obtained results which suggest that aging is accompanied by a loss in elementary local grouping mechanisms. While there is increasing evidence that the general holistic nature of face perception is maintained at mature ages (Konar et al, 2013 ; Meinhardt-Injac et al, 2014b ), recent findings suggest that adapting viewing strategies aided by feedback, coping with increased attentional demand and flexible handling of diagnostic cues are affected by aging (Meinhardt-Injac et al, 2014a ).…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, in the present study, face processing performance improved with age, particularly in the incongruent condition. Prior studies have indicated that the face processing performance of adults is considerably better than that of children (De Heering et al, 2007;Mondloch et al, 2007), and that of older adults (Meinhardt-Injac et al, 2014), especially in the incongruent condition. This is also consistent with prior indications that face processing performance develops with age (see Germine et al, 2011 for a review;McKone et al, 2012;Megreya and Bindemann, 2015) and with the general cognitive development theory of Crookes and Mckone (2009).…”
Section: Discussionmentioning
confidence: 95%